KONSEP DASAR PENGEMBANGAN POLA PIKIR PENDIDIK - Afrizal Afrizal (STAI Hubbulwathan Duri, 2015)
The fuction of Human Resources (HR) in supporting the success of organization work is dominant, so it should be implemented the increasing of the Human Resources Continuously. Educator (teacher) as the main Element of Human Resources and they they also have role to determine the success of the Implementation of Development. The Educators’ figure must have adequate Competences. They includes intellegencies, attitude and skills. To run their role optimally,it need to improve the competence continuously and sustainably. It is usually given by various exercises, seminars, Scientific Discussion. The activities is done to change the teachers’s mind as State apparatus that have function as public service